Effect of an educational intervention on manual toothbrush bristle wear: A light microscopic study - Siddhi Shekhar Bhole; Nupura A Vibhute; Uzma Belgaumi; Vidya Kadashetti; Sushma Bommanavar; Wasim Kamate (Wolters Kluwer Medknow Publications, 2022)
Background and Objectives: The usage of a toothbrush with the most appropriate bristle type and a correct brushing technique are the most important factors in determining the thoroughness of plaque control. The dental undergraduate course conventionally does not impart tooth brushing techniques in the preclinical years. This study aimed to assess the effect of an educational intervention of correct tooth brushing technique on the wear of toothbrush bristles by light microscopic examination amongst the budding dental professionals. Materials and Methods: Toothbrush bristle wear was measured by light microscopy before and after an educational intervention amongst 30 first-year dental professional students. Wear index (WI), wear rate (WR), and acceptable percentage of bristle end morphology were calculated. Mann-Whitney U-statistics test and unpaired t-test were used to compare measurements of acceptable percentage and gender wise, respectively. The difference was said to be significant if P < 0.05. Results: The mean WI before intervention was 0.29 ± 0.122 and after the intervention was 0.23 ± 0.07, while the mean WR before intervention was 1.6 ± 0.167 and after the intervention was 1.17 ± 0.46% of bristle end morphology before intervention was 52.5 ± 10.064 and after intervention was 64.5 ± 5.625 with the difference being statistically significant with P < 0.05. Interpretations and Conclusion: The present study highlights the importance of imparting a correct tooth brushing technique in reducing the toothbrush bristle wear and improving the efficiency of the toothbrush in maintaining optimum oral hygiene. Early intervention of correct oral hygiene measures is especially prudent for the budding dental professional for future healthcare delivery to the general population.